The Hematological Effects of Nitrous Oxide Anesthesia in Pediatric Patients. (June 2015) - Duma, Andreas; Cartmill, Christopher; Blood, Jane; Sharma, Anshuman; Kharasch, Evan D.; Nagele, Peter
<x xml:space="preserve">Abstract</x> BACKGROUND: Prolonged administration of nitrous oxide causes an increase in plasma homocysteine in children via vitamin B12 inactivation. However, it is unclear whether nitrous oxide doses used in clinical practice cause adverse hematological effects in pediatric patients. METHODS: This retrospective study included 54 pediatric patients undergoing elective spinal surgery: 41 received nitrous oxide throughout anesthesia (maintenance group), 9 received nitrous oxide for induction and/or emergence (induction/emergence group), and 4 did not receive nitrous oxide (nitrous oxide–free group). Complete blood counts obtained before and up to 4 days after surgery were assessed for anemia, macrocytosis/microcytosis, anisocytosis, hyperchromatosis/hypochromatosis, thrombocytopenia, and leukopenia. The change (Δ) from preoperative to the highest postoperative value was calculated for mean corpuscular volume (MCV) and red cell distribution width (RDW). RESULTS: No pancytopenia was present in any patient after surgery. All patients had postoperative anemia, and none had macrocytosis. Postoperative MCV (mean [99% confidence interval]) peaked at 86 fL (85–88 fL), 85 fL (81–89 fL), and 88 fL (80–96 fL) and postoperative RDW at 13.2% (12.8–13.5%), 13.3% (12.7–13.8%), and 13.0% (11.4–14.6%) for the maintenance group, the induction/emergence group, and the nitrous oxide–free group. Two patients in the maintenance group (5%) developed anisocytosis (RDW >14.6%), but none in the induction/emergence group or in the nitrous oxide–free group (P = 0.43). Both ΔMCV (P = 0.52) and ΔRDW (P = 0.16) were similar across all groups. CONCLUSIONS: Nitrous oxide exposure for up to 8 hours is not associated with megaloblastic anemia in pediatric patients undergoing major spinal surgery.